REACTIONS OF CISPLATIN HYDROLYTES WITH THIOLS. 3: REACTIONS OF cis-[Pt(15NH3)2(H2O)2] 2+ WITH GLUTATHIONE - Hadi, Hadi (Makara Journal of Science, 2006)
The reaction of cis-[Pt(15NH3)2(H2O)2] 2+ (3) with glutathione (GSH) was investigated in aqueous solution. In this reaction, the ammine in the platinum complex formed was liberated. Surprisingly two chelate rings were observed, six-membered-S,O-chelate ring complex cis-[Pt(15NH3 )2 (SG-S,O) (7) and five-membered-S,N-chelate ring complex cis-[Pt(15NH3 )2 (SG-S,N)] (8). The bis (thiolate) platinum(II) complex, cis-[Pt(15NH3 )2 (SG)2 ] (9) was always present in this reaction in any mole ratio used. The dinuclear sulphur-bridged complex (10), giving a broad peak in 15N NMR, was only present in very tiny amounts.